Edukasi Pada Pasien Covid Menggunakan Teknik Saji Terhadap Perubahan Pengetahuan, Motivasi dan Perilaku Kesembuhan Covid 19 di Ruang Isolasi Khusus Rumah Sakit Umum Karsa Husada Batu - Dwi Sulistiyanto; Katmini Katmini (Jurnal Imejing Diagnostik (JImeD), 2022)
Background: The implementation of health services is more focused on improving, maintaining, and protecting health, so it is not only focused on recovery or healing of diseases. Hospital as a referral level health service institution plays an important role in encouraging all stakeholders to commit to promotive and preventive efforts in preventing and reducing health risks faced by Patients, Patient Families, Hospital Human Resources, Hospital Visitors and the community, and to keep them in goodhealth. The purpose of the study to analyze the effectiveness of education in Covid 19 patients using SAJI techniques against changes in the knowledge, motivation and behavior of Covid 19 patients in the Special Isolation Room of Karsa Husada Batu General Hospital.Methods: Type of quantitative research with Pre-experimental design and One-Group Pretest-Posttest Research Design approach. The population of all covid 19 patients in isolation rooms amounted to 55 respondents. A sample of 46 respondents with Morgan's table, a total sampling technique. Independent variables of knowledge. Variable intervening motovation. Behavioral dependent variables.Results: There was a significant difference between knowledge before and after education (sig. = 0.000). There is a significant difference between motivation before and after education (sig. = 0.000). There is a significant difference between the behavior before and after education (sig. = 0.000). The motivation variable significantly serves as an intervening variable between the influence of knowledge variables on behavior (sig. = 0.01).Conclusions: It is hoped that by educating covid patients using present techniques can increase knowledge, motivation and behavior of Covid 19 recovery.